2020
DOI: 10.1111/ina.12703
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional study of in‐vehicle exposure to ultrafine particles and black carbon inside Lebanese taxicabs

Abstract: Taxi drivers' exposure to traffic-related air pollutants inside their vehicles has been reported in different countries but not yet in Lebanon. Thus, we conducted a crosssectional study on 20 Lebanese taxi drivers to (1) assess their exposure to ultrafine particles (UFP) and black carbon (BC) inside their vehicles and (2) identify determinants of this exposure. UFP and BC were measured using Diffusion Size Classifier Miniature ® and microAeth ® Model AE51, respectively, for 5 hours. Data on characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
1
10
0
3
Order By: Relevance
“…This result may indicate that cars with large displacement are equipped with advanced technology and they tend to have a better engine quality. 57 In contrast, high in-taxi NO 2 and CO levels were found in older and high-mileage vehicles, respectively, which corresponds with trends for CO concentrations found by Moreno et al 37 In total, taxi driver exposure to UFP, NO As with previous studies, 16,19,20,[35][36][37]46,[64][65][66] ventilation mode was found to be a key determinant of driver exposure to TRAP inside their vehicles. This study indicates that UFP and BC levels decreased considerably when windows were closed with AC mode on and their levels were much lower if ARM was activated.…”
Section: Vehicle Characteristicssupporting
confidence: 61%
See 1 more Smart Citation
“…This result may indicate that cars with large displacement are equipped with advanced technology and they tend to have a better engine quality. 57 In contrast, high in-taxi NO 2 and CO levels were found in older and high-mileage vehicles, respectively, which corresponds with trends for CO concentrations found by Moreno et al 37 In total, taxi driver exposure to UFP, NO As with previous studies, 16,19,20,[35][36][37]46,[64][65][66] ventilation mode was found to be a key determinant of driver exposure to TRAP inside their vehicles. This study indicates that UFP and BC levels decreased considerably when windows were closed with AC mode on and their levels were much lower if ARM was activated.…”
Section: Vehicle Characteristicssupporting
confidence: 61%
“…In general, mean concentrations of UFP and BC inside Parisian taxi vehicles were lower than those measured in the pilot study conducted inside Lebanese taxicabs (29.7 vs 35.2 × 10 3 particles/cm 3 , 3.1 vs 5.18 μg/m 3 , respectively) 35 . This is possibly because of the difference in vehicle age and fuel types used 36 in the two countries.…”
Section: Discussionmentioning
confidence: 55%
“…Only two of the studies reviewed (Baccarelli et al 2014;Davis et al 2007) sampled more than 80 shifts with the majority less than 20 and focussed on a single sector such as taxi, bus or truck drivers, making it difficult to assess whether these studies are representative of the industry as a whole. Only five out of the 16 studies employed time-resolved instrumentation (Gany et al 2017;Hachem et al 2020Hachem et al , 2021Lee et al 2015;Moreno et al 2019) using a portable aethalometer to measure BC at a 1-min time resolution. All other studies used time-integrated assessment for the duration of the drivers shift or for one study over a 24-h period.…”
Section: Professional Drivers and Occupational Exposure To Diesel Exhaustmentioning
confidence: 99%
“…The second study in New York City measured BC and PM 2.5 exposures to seven taxi cab drivers and found that in-vehicle exposures were almost double those of background monitors (Gany et al 2017). The three other studies measured 20 taxi driver shifts in Lebanon (Hachem et al 2020), 14 taxi driver shifts in Barcelona (Moreno et al 2019) and 50 taxi driver shifts in Paris (Hachem et al 2021) and suggested that drivers' BC exposure was affected by meteorology, vehicle type, window position and ventilation settings. Whilst these studies help illustrate the high exposures of drivers, the sample sizes are small and variations in design and monitoring make an integrative summary difficult.…”
Section: Professional Drivers and Occupational Exposure To Diesel Exhaustmentioning
confidence: 99%
“…Studies assessing personal exposure to a large range of aerosols metrics concurrently are still scarce. Many of the studies assessing personal exposures have focused on measuring one or two aerosol metrics [35][36][37][38][39], but studies reporting BC, PM 2.5 and UFP concurrently are very limited [40,41]. In addition, a comparative assessment of the influence of indoor and outdoor sources on the personal exposure to particulate matter is also very limited [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%